2016
DOI: 10.1637/11351-121715-reg
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Highly Pathogenic Avian Influenza H5N2 Infection on Table-Egg Layer Farms in the Midwestern United States, 2015

Abstract: A case-control study was conducted among commercial table-egg layer and pullet operations in Iowa and Nebraska, United States, to investigate potential risk factors for infection with highly pathogenic avian influenza (HPAI) H5N2. A questionnaire was developed and administered to 28 case farms and 31 control farms. Data were collected at the farm and barn levels, enabling two separate analyses to be performed-the first a farm-level comparison of case farms vs. control farms, and the second a barn-level compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 8 publications
1
29
1
1
Order By: Relevance
“…These environmental pathways are likely directly related to wild birds, as wild birds could spread virus in a manner consistent with the definition of k , i.e., independent of distance and the number of infectious premises. Indeed, wild waterfowl have often been suspected of causing the initial introduction into commercial poultry in previous outbreaks [ 27 ], and are suggested by Garber et al [ 28 ] as the likely source of initial introduction and spread into new areas during the 2015 HPAI outbreak in the United States. Ideally, since the spatial transmission kernel assumes infections are due to lateral spread, separate transmission kernels should be fit to each introduction and resulting infections as identified through a method such as phylogenetic clustering or mapping of epidemiological links.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These environmental pathways are likely directly related to wild birds, as wild birds could spread virus in a manner consistent with the definition of k , i.e., independent of distance and the number of infectious premises. Indeed, wild waterfowl have often been suspected of causing the initial introduction into commercial poultry in previous outbreaks [ 27 ], and are suggested by Garber et al [ 28 ] as the likely source of initial introduction and spread into new areas during the 2015 HPAI outbreak in the United States. Ideally, since the spatial transmission kernel assumes infections are due to lateral spread, separate transmission kernels should be fit to each introduction and resulting infections as identified through a method such as phylogenetic clustering or mapping of epidemiological links.…”
Section: Discussionmentioning
confidence: 99%
“…The distance dependent transmission kernel results suggest that local transmission pathways such as equipment sharing, or movement of wild animals (e.g., raccoons or foxes) or people between premises [ 29 , 30 ] contributed substantially to outbreak spread. However, the sizeable hazard rates estimated for extended distances from an infectious premises are evidence that contact occurring over moderate distances, for example garbage and/or rendering truck visits to multiple premises, in addition to the local contacts, may have contributed to between-premises HPAI spread during the Minnesota outbreak [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the 2014 outbreak of HPAIV H5N2, a case-control study of 59 layer farms in the mid-western part of the USA showed that 'low to moderate rodent severity' was significantly associated with case farms. In this study fly control was 'protective' against infection (Garber et al 2016). In a questionnaire administered to farms involved in the 2014-2015 outbreak of HPAIV H5N2 in the USA, one of the questions asked was whether rat and mouse bait stations were checked every six weeks.…”
Section: Association Of Rodents With Aiv Outbreaksmentioning
confidence: 99%
“…Garbage trucks coming near the barns (within 15 ft) were identified as a significant risk factor in a case–control study in the 2015 United States HPAI H5N2 outbreak. It was shown that egg layer flocks in Nebraska and Iowa that had garbage trucks coming near the barns were 14.7 times more likely to be infected (at the farm level) than flocks that did not have garbage trucks come near the barns ( p < 0.001) ( 2 ). Of note, the frequency with which garbage trucks visited the farms in this study is not known.…”
Section: Introductionmentioning
confidence: 99%